PENGARUH KOMPENSASI, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. ADIRA DINAMIKA MULTI FINANCE - Indah Edityawati, Mega (Sekolah Tinggi Ilmu Ekonomi GICI, 2023)
Human Resources (HR) is an important asset to support the success of an organization. The importance of human resources needs to be realized by all levels of management in the company. The purpose of this study is to determine and analyze the Effect of Compensation, Motivation and Work Discipline on Employee Performance of PT Adira Dinamika Multi Finance Tbk Bogor Branch 1. The type of research used is quantitative research with a survey method approach in the form of data collection using questionnaires. Sample selection is carried out using saturated sampling techniques. The sample amounted to 50 respondents, using multiple linear regression analysis. The regression test results showed that 71.40% of employee performance factors could be explained by compensation, motivation and work discipline while the remaining 28.60% were explained by other factors not studied in this study. While the results of the F test show that simultaneously the variables of compensation, motivation and work discipline have a significant effect on employee performance. The results of the t test show that the variables of compensation, motivation have a significant effect on the Employee Performance of PT Adira Dinamika Multi Finance Tbk Bogor Branch 1. The work discipline variable does not have a significant effect on the Employee Performance of PT Adira Dinamika Multi Finance Tbk Bogor Branch 1.